2007
DOI: 10.1051/0004-6361:20077443
|View full text |Cite
|
Sign up to set email alerts
|

A CFH12k lensing survey of X-ray luminous galaxy clusters

Abstract: Aims. We present a wide-field multi-color survey of a homogeneous sample of eleven clusters of galaxies for which we measure total masses and mass distributions from weak lensing. This sample, spanning a small range in both X-ray luminosity and redshift, is ideally suited to determining the normalisation of scaling relations between X-ray properties of clusters and their masses (the M − T X and the M − L X relations) and also estimating the scatter in these relations at a fixed luminosity. Methods. The eleven … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
143
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 82 publications
(152 citation statements)
references
References 105 publications
(169 reference statements)
6
143
3
Order By: Relevance
“…Previous studies tend to find a slope in the M − L relation that is slightly larger than one (Lin et al 2004;Popesso et al 2005;Bardeau et al 2007;Reyes et al 2008). This tendency is predicted by some of the semi-analytical models of galaxy formation, at least for massive clusters (Marinoni & Hudson 2002) in which the star formation efficiency can be inhibited by the long cooling times of hot gas on high-mass scales.…”
Section: Optical Scaling Lawsmentioning
confidence: 85%
See 2 more Smart Citations
“…Previous studies tend to find a slope in the M − L relation that is slightly larger than one (Lin et al 2004;Popesso et al 2005;Bardeau et al 2007;Reyes et al 2008). This tendency is predicted by some of the semi-analytical models of galaxy formation, at least for massive clusters (Marinoni & Hudson 2002) in which the star formation efficiency can be inhibited by the long cooling times of hot gas on high-mass scales.…”
Section: Optical Scaling Lawsmentioning
confidence: 85%
“…To correct for the PSF smearing, we use the Im2shape software (Bridle et al 2002), which has already demonstrated its potential to recover the intrinsic shape of the galaxies (Cypriano et al 2004;Bardeau et al 2005Bardeau et al , 2007Limousin et al 2007a,b). Starting with a given model for the shape of each object, the code convolves it with the local estimate of the PSF.…”
Section: Object Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…This software performs an analytical deconvolution of the galaxy images, approximated by a single elliptical Gaussian, and returns the intrinsic shape parameters with their uncertainties, estimated by a Bayesian analysis of the image residuals. It has been successfully applied on a sample of clusters of galaxies by Bardeau et al (2007), who developed a methodology for the shear analysis that we follow fairly closely. To test the validity of the analysis chain, we checked that the result of the deconvolution process applied to the stellar field itself shrinks the size of the deconvolved stars to less than 0.1 , with a flat distribution of their orientation (Fig.…”
Section: Psf Correction and Galaxy Shape Measurementsmentioning
confidence: 99%
“…The methodology used in this work follows Bardeau et al (2007), also applied by Limousin et al (2009) on the first SL2S group sample. A full description of the procedure can be found in Foëx et al (2012), and of its applications in the last SL2S sample in Foëx et al (2013).…”
Section: Weak Lensing Methodsmentioning
confidence: 99%